PENGENALAN STRUKTUR DAN SIFAT FISIK BAHAN PRODUK TANAMAN BAMBU PADA KELOMPOK TANI DESA URENG, KABUPATEN MALUKU TENGAH - Fransz, Jimmy Johanson (Universitas Pattimura, 2024)
Bamboo is a non-timber forest product that is abundant in tropical and subtropical regions of Asia, thriving in areas with high rainfall. In Indonesia, bamboo can be found in lowland to mountainous areas, typically growing in open spaces. In Ureng Village, bamboo has yet to significantly contribute to improving the local community’s welfare. One of the main factors limiting the optimal utilization of bamboo is the lack of knowledge regarding the physical properties and characteristics of bamboo wood, which could be processed into various economically valuable products. This activity aimed to provide education on the structure and properties of bamboo wood to enhance the economic value for the Ureng Village community. The results show that participants were highly enthusiastic about learning the properties and structure of bamboo wood, which can enable them to utilize bamboo as a substitute for timber.